Svenska livsmedel - varför? - Lindberg, Andreas; Petersson, Richard (2005)
The background of this research is that Swedish food products have hard to compete at the home market, depending on imported food products that increase more and more for every year that pass by. The ethic values LRF associate with Swedish food products, many customers have hard to put in relation with condition of foreign agriculture. Most customers today inquire high quality, safety and convenience in the food which they are eating. The source of their food seems to have less meaning. Many restaurants and bigger households appreciate Swedish food products and wants to buy them but price differences against foreign wares are to high. We have done oral interviews with wholesale dealers, restaurants, public purchasers and with different market organisations, there we have discussed buying strategies, the way they see the primary producer, the conscious of guests, choice and attitudes to Swedish and foreign products, distribution of power in the food market chain and to what position and suspension, they want the ranks of suppliers to have. The result shows the share of imported wares within restaurants and bigger households are at a high level and will continuing increasing. Within these sectors the final consumer in many cases put less effort in the origin of the raw source of food. What the company and the branch really appreciate from primary producers are high quality, high level of service with frequent deliveries, convenience and competitive prices on the products. To be able to put on high price values on raw food the guest must feel a immediate association with these values in for example the local environment, to do this group of costumers interested in paying a higher price. A possibility for primary producers to increase their focus on the costumers is to create and build up a network together with other suppliers to offer a wider product mix of local produced wares. There must be an entrepreneur who is head of this network, that joins all the suppliers together and at the same time can offer a comfortable concept for restaurants and bigger households, that create interest and conscious for domestic products.